Zarządzanie siecią dostaw jako czynnik internacjonalizacji przedsiębiorstwa - Rodawski, Bartłomiej (Management of distribution network as a factor of firm's internationalization, 2005)
In the paper the network approach to internationalization of enterprise is presented. According to the model, internationalization is a process of establishing, developing and coordinating relationships with foreign supply network partners. Consequently supply network management, and supply network itself can be considered as one of the internationalization factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 191-198